Penta Helix Collaboration in Higher Education - Adisaputra, Ateng Kusnandar (Lentera Barasaki Publishing House, 2023)
The aim of this paper is to analyze penta helix collaboration in higher education. Universities are being faced with changes driven by innovation in science and technology, namely the industrial era 4.0 , making universities continue to encourage themselves to adapt and innovate to environmental changes in order to survive and exist in the journey of developing educational services. The research method used by literature studies ( library research ) is the basis of this paper. The analysis was carried out using qualitative descriptive analysis methods. Analysis results using the penta helix. First , from the government aspect , each university can collaborate internally and externally, namely with Central Government institutions, Provincial Regional Governments and Regency/City Regional Governments, of course as sub-ordinates of the structure of the Government of the Republic of Indonesia. Second, each university can collaborate with academics from various universities and study program associations. Third, on the aspect of society/ communities , Each university can collaborate with alumni and optimize the community service (PKM) section. Fourth, in the business aspect , each university can collaborate with relevant companies. Fifth , mass media is not only optimized internally like websites and other official accounts. However, there is a need for cooperation with other media as mediators to socialize and distribute educational programs